Sensitivity of acoustic emission amplitude-energy parameters to change in properties of treated composite - Филоненко, Сергей Федорович (Eastern-European Journal of Enterprise Technologies, 2015)
Control and monitoring of composite machining is an important task in ensuring the quality of manufactured products. One of the ways to solve the problem is using the acoustic emission method. Modeling of the change in the energy of acoustic emission signals in the composite machining, depending on the parameter that is determined by its properties was considered. Data processing showed that the increase in the influencing parameter leads to a drop in acoustic emission energy parameters. Herewith, the dispersion with an average energy level of the generated signal has the largest drop. Comparison of changes in the acoustic emission energy-amplitude parameters showed that with the increasing influencing factor, percent drop of dispersion of the average energy level outstrips the percent drop of its average level and standard deviation, as well as all the amplitude parameters of acoustic emission signals. The results show that the dispersion of the average energy level of acoustic emission signals can be used to develop methods for control, diagnosing and monitoring of the unevenness of the surface properties of manufactured products in the composite machining process.